THE IMPACT OF GASOLINE-TO-LPG FUEL CONVERSION ON ENGINE PERFORMANCE IN ELECTRONIC FUEL INJECTION MOTORCYCLES: AN EXPERIMENTAL ANALYSIS - Sentosa, Ilham; Mukarrama, St. Khaeratul (Universitas Negeri Yogyakarta, 2025)
This study aims to determine the performance analysis in converting gasoline fuel to LPG fuel on motor performance on electric fuel injection-based motorcycles and engine performance with the use of LPG gas fuel and gasoline. with a 110 cc engine at engine speeds of 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 and 5000 rpm. Instrument testing was carried out at Ernest Racing Home (Makassar). This research method is